Temperature Fluid Flow of Particles with The Effect of Magnetic Field in A Cylindrical Polar Coordinates of Incompressible Dusty Fluid - Jagannadham, N.; Rath, B. K.; Dash, D. K. (International Journal of Membrane Science and Technology, 2023)
The effects of temperature of dusty fluid flow in a weak magnetic field are investigated in this paper. The motion of dusty fluid is affected by a homogeneous magnetic field that runs in the same direction as the fluid. Parameters include longitudinal velocity, Hartmann number; dust particle interactions, stock resistance, Reynolds number, and magnetic Reynolds number fully characterize the topic that is being studied. The obtained partial differential equations are translated into an ode system using appropriate similarity transformations. To solve these equations numerically we use, the Laplace Transform technique. The result shows the temperature of fluid particle reduced significantly in the magnetic field.